Seeded growth synthesis of gold nanorods for photothermal application - Do Thi Hue; Duong, Vu Thi Thuy; Nghia, Nguyen Trong; Nhung , Tran Hong; Nghiem Thi Ha Lien (Vietnam Journal of Science and Technology, 2018)
In this paper, the gold nanorods (GNRs) were synthesized via a seed-mediated method using 1-3 nm seeds-in diameter and gold atoms created from the reduced Au3+ ions by ascorbic acid (AA) in the presence of cetyltrimethylammonnium bromide (CTAB) as a surfactant templating. The aspect ratio of GNRs as well as growth yield was controlled by adjusting the concentration of Ag+ ions.